Malawi : Report on the Observance of Standards and Codes-Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper presents report on the Observance of Standards and Codes-Fiscal Transparency Module for Malawi. A number of improvements have been made to budget management in Malawi in recent years that are increasing the level of fiscal transparency. Notable examples include the development of a sophisticated budget classification system and the introduction of the Medium-Term Expenditure Framework (MTEF) budgeting process. However, the developments have not been applied consistently across the different areas of fiscal management, and there has been insufficient attention to data quality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet